Immigrant women’s food choices in pregnancy: perspectives from women of Chinese origin in Canada - Higginbottom, G.M.A.; Vallianatos, Helen; Shankar, Janki; Safipour, Jalal; Davey, Christina (Tayor Francis, 2017)
Objective: Following migration, pregnant immigrant women may encounter social, cultural, and economic challenges that negatively affect their food choices and subsequent health outcomes. Culturally appropriate health care is crucial during the perinatal period to ensure the health of immigrant mothers and their children. This project aims to explore and understand how the health beliefs and practices of Chinese immigrant women affect their food choices during the perinatal period.